Structure and diversity of intestinal methanogens in black carp (Mylopharyngodon piceus), grass carp (Ctenopharyngodon idella) and water samples - Chengxing Long; Peiyang Wang; Jieqi Wu; Jialin Liu; Zhoujin Tan; Wenge Li (PLoS ONE, 2025)
The present research investigation aims to examine the community features of methanogens in the intestinal tract of black and grass carp, as well as their association with methanogens in water samples. Samples of black carp, grass carp and water in a pond were gathered in Spring 2021. Using the Illumina HiSeq 2500 high-throughput sequencing platform, the metagenomic mcrA gene sequences of black carp, grass carp and cultured water specimens were determined and analyzed. The outcomes indicate that the richness and diversity of methanogens in the intestinal tract of black and carp grass carp were highly correlated with the cultured water. Five bacterial genera were found in the three sets of samples, Methanosarcina, Methanocorpusculum, Methanospirillum, Methanobacterium and Methanofollis, in which Methanosarcina and Methanocorpusculum were the dominant genera. In addition, Methanosarcina had the greatest amount in grass carp and Methanocorpusculum had the greatest quantity in black carp. In conclusion, Methanosarcina and Methanocorpusculum were the main methanogens in the digestive tract of black and grass carp and culture water, and hydrolytic fermentative bacteria were its main metabolic substrate, hydrotrophic was its main metabolic pathway. The results will provide a reference for the relationship between intestinal methanogens and aquaculture and the greenhouse effect.